Analisis Perkerasan Kaku (Rigid Pavement) dengan Mutu Beton Fs’45 terhadap Kuat Tekan dan Lentur: Studi Kasus: Rekonstruksi Ruas Jalan Baros-Petir - Setiawan, Riki; Supratman, Odih (Teknik Sipil, Politeknik Negeri Ketapangg, 2025)
This study aims to analyze the use of FS 45-grade concrete in rigid pavement for the reconstruction of the Baros-Petir Road. FS 45 concrete, with a minimum compressive strength of 45 MPa and flexural strength of 5–6 MPa, is designed to withstand heavy traffic loads, particularly from vehicles such as trucks. Testing involved the analysis of compressive and flexural strength using cylindrical samples (150 mm in diameter and 300 mm in height) and beam samples (150 mm x 150 mm x 600 mm) at 7 and 28 days. The concrete mixing process followed a Design Mix Formula, ensuring optimal material proportions and strength. Results revealed that FS 45 concrete achieved an average compressive strength of 42.81 MPa and an average flexural strength of 5.5 MPa, meeting the minimum quality standards of 39.7 MPa and 4.4 MPa, respectively. The concrete demonstrated excellent durability against heavy traffic loads, enhanced the pavement's service life, and reduced long-term maintenance costs. Factors such as subgrade conditions, drainage systems, and construction processes were identified as critical elements for successful rigid pavement implementation. This research contributes significantly to improving transportation infrastructure, offering a more durable and efficient solution, particularly for roads with high traffic intensity.